Analisis Faktor Produksi Cabai Merah (Capsicum Annum L.) Di Kecamatan Beringin Sebagai Sentra Produksi Di Kabupaten Deli Serdang - Ramadhona, Yulviane; Siregar, Akbar; Effendi, Ihsan (JURNAL AGRICA, 2024)
The demand for red chillies from both North Sumatra and outside North Sumatra is high, but farmers in Deli Serdang Regency the main producing area for red chillies have not been able to meet it. This study aims to analyze production factors of red chili production in Beringin District as a production centre in Deli Serdang Regency. The population of this study was the Juli Farmer Group in Beringin District, Deli Serdang Regency. The selection of this sample used simple random sampling so the sample obtained was 83 respondents from the Juli Farmer Group. The analysis tool used was multiple linear regression with the Cobb-Douglas model. The results of the study showed that production factors in the form of labor, land area, and capital had a significant effect on red chili production, while technology costs did not affect red chili production in Beringin District, Deli Serdang Regency. So it is hoped that with the addition of land area and capital and labor will increase red chili production and can meet market demand.